Advances in Data-Driven Marketing Technologies: A Bibliometric Analysis of Indonesian Research Trends - Yuaniko Paramitra; Syamsu Rijal; Guellica Agnesia Claudia Thanos; Toong Hai Sam; Intan Nurrachmi; Darwis Robinson Manalu; Rahim, Robbi (PT Mattawang Mediatama Solution, 2024)
Indonesia, the largest economy in Southeast Asia, has experienced an increase in need for innovative, data-driven marketing research given its fast economic expansion. Business strategy and decision making depend on this study as it let companies adjust to the specificities of local markets affected by socioeconomic, technological, and demographic variables. This study aims to assess the direction and breadth of the research as well as identify any knowledge gaps or underutilized studies in the field of marketing, especially in Indonesia. Bibliometrics is the technique utilized by means of data analysis drawn from the Scopus database in January 2024. Ratih Hurriyati of the Indonesian Education University, with 11 publications to her credit and 209 citations to her works, is the most active writer in this area. The results show the key trends in Indonesian marketing research. Apart from that, the